Evidence of bank lending channel in Malaysia - Said, Fathin Faizah; Ismail, Abdul Ghafar (Universiti Utara Malaysia, 2008)
The aim of this paper is to analyse the role of banks in the transmission of monetary policy and business cycle. This paper attempts to look into the assets side as a monetary policy channel to influence economic activities. Changes in the monetary policy channel give an idea to regulate and strengthen the banking industry. The different views raise the following questions: how do changes in the monetary policy transmission affect commercial banks portfolio? If bank lending plays as a monetary policy channel, does it affect the other portfolios? Do the current regulations (such as capital requirement)affect the bank portfolio behaviour? Furthermore, Generalise Least Squares method was used to estimate the monetary changes toward commercial banks portfolio. Annual data was compiled from the year 1994 until 2004. The number of observations was based on the combination of time series and cross-sectional data, which is known as pooled data. In addition, an unbalanced bank-level panel data set for commercial banks was used. Finally, our results found that there exists a bank-lending channel in the case of Malaysia.